Early adaptation to heat waves and future reduction of air-conditioning energy use in Paris - Vincent Viguié; Aude Lemonsu; Stéphane Hallegatte; Anne-Lise Beaulant; Colette Marchadier; Valéry Masson; Grégoire Pigeon; Jean-Luc Salagnac (Environmental Research Letters, 2020)
Some actions intended to adapt to climate change may do more harm than good, especially when they consume energy, making it more difficult to shift to decarbonized energy, or when, in meeting the needs of one group of people, they increase the vulnerability of others. Heat wave risk provides a typical example: air conditioning (AC) equipment may trigger large energy consumption and worsen outdoor heat stress. Alternative adaptation strategies exist, but it is not clear whether they can prevent the massive use of AC. Here, with an interdisciplinary modeling platform, taking Paris as a case study, we provide a first quantified analysis of the efficiency of adaptation strategies (large scale urban greening, building insulation policy, and generalized behavioral changes in AC use) in reducing future potential AC need. We find that even ambitious strategies do not appear sufficient to totally replace AC and ensure thermal comfort, under a median climate change scenario. They can, however, reduce AC energy use by half during heat waves and compensate for the heat released to the outdoor environment. Our results show that adaptation actions, implemented early, may play a key role if we are to remain on a low-carbon pathway.